FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN DIARE PADA BATITA DI WILAYAH KERJA PUSKESMAS HARAPAN BARUKECAMATAN LOA JANAN ILIR KOTA SAMARINDA TAHUN 2017 - Linda Amalia (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
Diarrhea is environmentally based disease and occur in almost all geographic regions of the world. There are several factors associated with diarrhea that mother's knowledge, inadequate water supply, water contaminated by feces, lack of sanitation, unhygienic excreta disposal, personal hygiene, sociodemographic, unfavorable environment.  The Children have susceptibility to an illness. This vulnerability is not only caused by their immune system but also influenced by their own environment. This research is an analytical survey research using Case-Control research design. The sample for the case was 29 and for the control of 29 using the Slovin formula. Data were analyzed by Chi-Square test with ? = 0.05. The result showed that there was no correlation between the level of knowledge with diarrhea (p = 0,070), there is no relationship between personal hygiene and diarrhea (p = 0,893), there is a relation between basic sanitation facilities (garbage and SPAL p = 0,019), and there is a relationship between exclusive breastfeeding and diarrhea (p = 0,000). It is concluded that there is a relationship between basic sanitation facilities (garbage   and   SPAL), and   there   is   a   relationship   exclusive breastfeeding and diarrhea in toddlers in the work area of Puskesmas Harapan Baru Village Loa Janan Ilir Samarinda city. It is advisable to the surrounding community to be able to use the trash closed, do not litter and making sewerage, and for breastfeeding mothers to be aware of the importance of exclusive breastfeeding for at least 6 months of age which has an effect on the immune system, especially on diarrhea.